Cash Sales System In CV. Cipta Kreasi Furniture Using Visual Basic 6.0, Microsoft Access 2003, and Crystal Report 8.5 - Radytiawan Rachmad, 30403128 (Jurnal Sistem Informasi, 2007)
Creative CV.Cipta Furniture is a store that sells a variety of furniture items, because the process manually the process is still in the process is judged to be ineffective and inefficient because of frequent errors caused by human error, it is necessary to increase the effectiveness of  computerization  and  efficiency  in  speed  running  of  the  company.  To mempermudahpekerjaan  required  in  terms  of  sales  and  computer  application  programs pemergraman language Microsoft Visual Basic 6.0, developed from the language Basic. Microsoft Visual Basic 6.0 programming language that is based Visual Programing and easy to use in making an application. Microsoft Access 2003 as a medium to create a database because of the ease given, and Crystal Report 8.5 as a medium to make a report. Based on the author for analysis, these enterprises in the administrative process in the sale is still done manually like create invoices and reports that support the course of the company. In this case there are several ways to solve these problems, including Document Flow of the proposed, context diagram, diagram of zero, Entity Relationship Diagram, Normalization and Design Input Output program that will be made with supporting software Microsoft Visual Basic 6.0